The Effect of Customer Value, Customer Experience, and Customer Preference on the Utilization of Inpatient Care Facilities: A Cross-Sectional Study - Rohilatul Jannah; Moh. Soleh; Thinni Nurul Rochmah; Raissa Manika Purwaningtias (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
The prevalence of outpatient care patients increased from 56.3% to 72.3%, while inpatient care patients significantly decreased from 5.2% to 1.9% from 2018 to 2019 in Bangkalan Regency. This study aims to analyze the effect of customer values, customer experience, and preference on the utilization of Inpatient Care Facilities in Public Hospitals. This study is an analytical observation with a cross-sectional design. Two hundred twenty respondents were included and chosen by simple random sampling.  The result showed that 44.5% of customer value was negative with a p-value of 0.0001; the proportion of customer experience at the sense level was 33.4% with a p-value of 0.0001; the highest proportion of customer preference was 27.3% for Service Quality and 20.9% for Good Doctors with a p-value of 0.0001. Customer value, customer experience, and preference significantly affected inpatient care facility utilization in Public Hospitals in Bangkalan Regency. This study recommends structuring a unique selling point based on the people’s needs using marketing sense to improve customer experience, paying attention to Service Quality, and using the Good Doctor as one of the important criteria in hiring doctors in a hospital.